2013
DOI: 10.1186/1743-422x-10-27
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of hepatitis B virus genotype C/C1 in the Minangkabau ethnic group in Indonesia

Abstract: BackgroundThe Minangkabau is one of the major ethnic groups in Indonesia. Previous studies with a limited number of samples have shown a different prevalence of HBV/C in the Minangkabau compared to the Indonesian population in general. The aim of this study was to assess the HBV genotype distribution pattern and the prevalence of pre-S, T1753V and A1762T/G1764A mutations among the Minangkabau HBV carriers. The samples were collected from Padang, West Sumatera and from western Java. Mixed primers for specific g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…In the present study, most OBI genomes were genotype B3. This is in accordance with previous studies showing that in Indonesia the most common HBV genotype is HBV B3 (HBV/B3), followed by HBV/C1, especially in Java island [ 21 , 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, most OBI genomes were genotype B3. This is in accordance with previous studies showing that in Indonesia the most common HBV genotype is HBV B3 (HBV/B3), followed by HBV/C1, especially in Java island [ 21 , 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…4,40 An accordance to previous research, genotype C is the most abundant in Minangkabau ethnic group and is associated with social interactions among the ethnic. 41 Recent study in Pekanbaru revealed that the pattern domination of genotype C. 42 These findings support the idea that geography and ethnicity influence the distribution of HBV genotypes.…”
Section: Discussionmentioning
confidence: 58%
“…This is due to specific mutations in the BCP promoter and pre-Core region which are also linked to an increased risk of HCC. 41,[44][45][46] These genotypes also cause differences in HBV therapy response and resistance. Genotype B responded better to interferon (IFN)-and Lamivudine therapy than genotype C. 47 Patients infected with genotype C were more likely to respond to pegylated interferon (PEG-IFN) than standard IFN.…”
Section: Discussionmentioning
confidence: 99%
“…This sequence similarity between HBV genotype B and C is also observed in another study. 17 In this study, we designed sgRNA, especially the CRISPR RNA (crRNA) that is complementary to the target DNA using in silico method. The sgRNA region that we proposed was located in 336-359 bases.…”
Section: Discussionmentioning
confidence: 99%